Upad delovne sposobnosti pri starejših medicinskih sestrah - Sečnjak, Bojana (Obzornik zdravstvene nege, 2025)
Introduction: The work ability in older nurses is often associated with stress and burnout in the workplace, the complexity of work duties and specific working conditions. The aim of this literature review was to examine and present current findings from the field of research on older nurses' work ability.Methods: This literature review on the work ability of older nurses was conducted on the basis of a systematic analysis of scientific articles published between 2012 and 2022. The review and analysis included articles available in full text and indexed in the PubMed Central, Science Direct, and Cochrane Library bibliographic databases, as well as in Google Scholar. Results: The literature search produced a total of1181 hits, of which eight articles were included in the final analysis. The review of the current findings on this topic detected three thematic areas, namely: 1) work ability and burnout, 2) work ability and work environment, 3) work ability and the model of selection, optimisation, and compensation. Discussion and conclusion: The work ability in nurses decreases with age. Based on the findings in the literature reviewed, we can conclude that the work ability of older nurses is insufficiently researched. With the ageing population of employed nurses and the demanding work conditions in the profession, this literature review provides the basis for further research in the field of nursing staff development.
Keywords: aging; nursing; older employees; staranje; starejši zaposleni; zdravstvena nega